QUEM PARTICIPA QUER (SE) INFORMAR? CARACTERÍSTICAS DO CONTEÚDO COMPARTILHADO EM GRUPOS DE WHATSAPP NAS ELEIÇÕES DE 2020, EM IMPERATRIZ – MARANHÃO. - SILVA, Luana Fonseca (2022)
This thesis analyzes the electoral campaign carried out by supporters of mayoral candidates in Imperatriz-MA, in 2020, through public WhatsApp groups, noting that the app became a vehicle for sharing political content in Brazil, notably from 2018. The aim of the research is to analyze the information that circulated in those groups, from the shared links, verifying the main characteristics of this information to understand the campaign. The choice for the app was due to its importance in the 2018 elections, as one of the main information channels not only during this period, but also at other times before and after it. Methodologically, quantitative and qualitative Content Analysis (CA) is used to investigate 342 sources of information shared in 13 WhatsApp groups: 4 support groups for the candidate Assis Ramos (MDB), 1 group for Marco Aurélio (PC do B), 2 groups for Sebastião Madeira (PSDB), 2 groups for Ildon Marques (PP), 1 group for Mariana Carvalho (PSC), 1 group for Daniel Fiim (PODE) and 2 support groups for Daniel Vieira (PRTB). No support groups were found for the other three candidates, Aluízio Melo (PSOL), Manoel Garimpeiro (PMB) and Sandro Ricardo (PCB). The analysis comprises the official time of the electoral campaign, from 09/27 to 11/15/2020, the date on which the voting took place. As a result, it can be said that the main sources of information are blogs, such as Blog Rui Porão, and the candidates' advisors. There are links that include news about President Jair Bolsonaro, both from his own social networks and news portals. In addition, content in video stands out in relation to other formats, there is intense use of Instagram as a source of information by the electorate in this environment, local and national news being highlighted in terms of coverage, and themes focused on political propaganda, including attacks on opponents, especially the one considered to be on the political left.